PEMBERIAN BEBERAPA DOSIS PUPUK MULTICOTE TERHADAP PERTUMBUHAN AKASIA (Acacia mangium) DI PEMBIBITAN - Elfarisna, Elfarisna; Setijorini, Ludivica Endang (LPPM Universitas Terbuka, 2013)
This study aims to determine the use of some dose of Multicote’s fertilizer on the growth of Acacia mangium seedlings and get the most effective dose of Multicote’s fertilizer in increasing the growth of Acacia mangium seedlings in the nursery. The study was conducted in May to July 2012, at the Faculty of Agriculture Experimental Farm, of Muhammadiyah’s University in Jakarta. The design used in this study is a randomized block design (RBD), with six dose treatments of Multicote fertilizer are: 0 g / plant (control), 2 g / plant, 4 g / plant, 6 g / plant, 8 g / plant, and 10 g / plant, each treatment was repeated four times. The parameters measured were height of plant, percentage of growth, wet weight and dry weight of plants. The research results showed that the treatment given was not significantly different on the height of plant height at the initial growth (4 MST, 6 MST and 8 MST), but at end of the observation (10 MST and 12 MST) showed that the treatment was  significantly different on the height of the plant. Of all the treatment given, the use of 10 g / plant of multicote is feltilizer gave the best effect on the height of plant, wet weight and dry weight of plant acacia. Control treatment without fertilizer multicote give the least influence on plant height, wet weight and dry weight of plant acacia’s plant. Penelitian ini bertujuan mendapatkan dosis pupuk Multicote yang paling efektif dalam meningkatkan pertumbuhan bibit Acacia mangium di pembibitan. Penelitian dilaksanakan pada bulan Mei sampai dengan bulan Juli 2012, di Kebun Percobaan Fakultas Pertanian Universitas Muhammadiyah Jakarta. Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok (RAK), dengan enam perlakuan dosis pupuk Multicote yaitu :  0 g/tanaman (kontrol), 2 g/tanaman, 4 g/tanaman, 6 g/tanaman, 8 g/tanaman, dan 10 g/tanaman, setiap perlakuan diulang empat kali. Parameter yang diamati adalah tinggi tanaman, persentase tumbuh, bobot basah tanaman dan bobot kering tanaman. Hasil penelitian menunjukkan pada pertumbuhan awal (4 MST, 6 MST dan 8 MST), perlakuan yang diberikan tidak memberikan pengaruh yang berbeda nyata terhadap tinggi tanaman. Namun di akhir pengamatan (10 MST dan 12 MST), perlakuan yang diberikan memberikan pengaruh yang berbeda nyata terhadap tinggi tanaman. Penggunaan pupuk Multicote dengan dosis 10 g/tanaman memberikan pengaruh yang paling baik terhadap tinggi tanaman, bobot basah dan bobot kering tanaman Akasia. Tanpa pupuk Multicote tinggi tanaman, bobot basah dan bobot kering tanaman Akasia adalah yang paling rendah.